Princess Mononoke - Miyazaki, Hayao 1941-; Anderson, Gillian 1968-; Crudup, Billy 1968-; Danes, Claire 1979-; Driver, Minnie 1970-; Pinkett Smith, Jada 1971-; Thornton, Billy Bob 1955-; Suzuki, Toshio 1948- (The Studio Ghibli collection, 2006)
Young warrior Ashitaka receives a wound that refuses to heal. Searching for a remedy, he leaves his remote village for the forbidding forests of the west